دراسة أسباب الانسدادات المعوية الميكانيكية وطرق تشخيصها عند البالغين - مسعود, سجيع; علي, ماجد; يونس, سومر (Latakia University Journal -Medical Sciences Series, 2017)
هدف البحث الى إجراء مقاربة إحصائية لأسباب انسداد الأمعاء الميكانيكي حسب تواردها وشيوعها, وتبيان أهمية التشخيص الباكر لها في تحسين نتائج التدبير. تضمنت عينة الدراسة 287 مريضاً بالغاً قبلوا في قسم الجراحة في مستشفى الأسد الجامعي باللاذقية بسبب انسداد معوي ميكانيكي, من بداية شهر كانون الثاني عام 2010 ولغاية نهاية آب عام 2015. كان عدد الذكور 186 مريضاً, بينما بلغ عدد الاناث 101 مريضة. وجد الانسداد الميكانيكي في الأمعاء الدقيقة لدى 253 مريضاً, بينما وجد في الأمعاء الغليظة لدى 34 مريضاً. تراوحت أعمار المرضى بين 21-88 سنة وكان نصف المرضى تقريباً في العقدين الثالث والرابع من العمر. أهم عرض راجع به المرضى هو توقف خروج الغازات والغائط وتكرر بنسبة 86.7% من الحالات, وكانت صورة البطن البسيطة بوضعية الوقوف أكثر الوسائل التشخيصية استخداماً, حيث أجريت عند حوالي 98% من المرضى. وجدنا أن معظم أسباب الانسداد المعوي الميكانيكي (73.51%) كانت بسبب الالتصاقات, تلتها الفتوق(12.19%), ثم الأورام(6.28%),أما بقية الأسباب كالانفتال والانغلاف وداء كرون والتهاب الرتوج فقد بلغت مجتمعة(8%) من المرضى.The research aims to make a statistical approach to the causes of mechanical intestinal obstruction by its incidence and demonstrating the importance of early diagnosis in improving the outcome of management.The study included 287 adults patient admitted in the department of surgery at AL-ASSAD University Hospital in Lattakia, due to mechanical intestinal obstruction, from the beginning of January 2010 until the end of August 2015.186 of patients were males and 101 were females. The obstruction was in the small bowel at 253 patients, while there were 34 cases in the large bowel. The patients ages were between 21-88 years and almost half of the patients were in their third and fourth decades of life. The most important symptom was stopping the release of gas and feces and was found in 86.7% of cases. The abdomen X-ray was the most diagnostic procedure we used, it was done for 98% of patients. Adhesions were the most common cause of intestinal obstruction (73.51%), it followed by hernias (12.19%), tumors (6.28%), while the rest of the reasons like volvulus, intussusception, Crohn's disease and diverticulitis were amounted (8%) of patients.